Reformulating Governor Elections between Popular Sovereignty and Government Effectiveness in Indonesia’s Decentralised System - Hasanudin, Maulana; Neni Ruhaeni; Efik Yusdiansah; Nurul Chotidjah (Universitas Islam Negeri Walisongo Semarang, 2025)
This study comprehensively examines the design of gubernatorial elections in Indonesia within the framework of decentralisation, with a particular focus on balancing the principle of popular sovereignty and the demands of local government effectiveness. Through a normative legal approach, juridical-deductive analysis, and a comparative constitutional study of the United States, Germany, India, Brazil, and the Philippines, this article evaluates the impact of the current design of gubernatorial elections on these two pillars. The main findings show that while direct gubernatorial elections formally affirm popular sovereignty, their implementation is faced with various juridical and political challenges such as money politics, dynastic politics, and party cartelisation that significantly delegitimized the essence of such sovereignty and undermine the effectiveness of local governance. The comparative analysis offers a spectrum of subnational local government election models, from direct elections to parliamentary appointments, whose success depends largely on the socio-political and constitutional context of each country. Based on these findings, the research recommends a series of multi-faceted reforms that touch not only on the electoral mechanism, but also on campaign finance regulation, political party institutional strengthening, and electoral law enforcement, in order to realise an ideal gubernatorial election design capable of strengthening the quality of democracy and the effectiveness of local governance in Indonesia. Penelitian ini mengkaji secara komprehensif desain pemilihan gubernur di Indonesia dalam kerangka desentralisasi, dengan fokus utama pada upaya menyeimbangkan prinsip kedaulatan rakyat dan tuntutan efektivitas pemerintahan daerah. Melalui pendekatan hukum normatif, analisis yuridis-deduktif, dan studi perbandingan konstitusional terhadap Amerika Serikat, Jerman, India, Brasil, dan Filipina, artikel ini mengevaluasi dampak desain pemilihan gubernur saat ini terhadap kedua pilar tersebut. Temuan utama menunjukkan bahwa meskipun pemilihan langsung gubernur secara formal mengafirmasi kedaulatan rakyat, implementasinya dihadapkan pada berbagai tantangan yuridis dan politis seperti politik uang, politik dinasti, dan kartelisasi partai yang secara signifikan mendelegitimasi esensi kedaulatan tersebut dan melemahkan efektivitas pemerintahan daerah. Analisis komparatif menawarkan spektrum model pemilihan kepala daerah sub-nasional, dari pemilihan langsung hingga penunjukan parlementer, yang keberhasilannya sangat bergantung pada konteks sosio-politik dan konstitusional masing-masing negara. Berdasarkan temuan ini, penelitian merekomendasikan serangkaian reformasi multi-aspek yang tidak hanya menyentuh mekanisme pemilihan, tetapi juga regulasi pendanaan kampanye, penguatan institusi partai politik, dan penegakan hukum pemilu, guna mewujudkan desain pemilihan gubernur yang ideal, yang mampu memperkuat kualitas demokrasi dan efektivitas pemerintahan daerah di Indonesia. Keywords: Governor Election; Popular Sovereignty; Election System; Regional Head Election.